RFID analysis of the complexity of cellular pathology workflow—An opportunity for digital pathology - Browning, Lisa; White, Kieron; Siiankoski, Darrin; Colling, Richard; Roskell, Derek; Fryer, Eve; Hemsworth, Helen; Roberts-Gant, Sharon; Roelofsen, Ruud; Rittscher, Jens; Verrill, Clare (Frontiers in Medicine, 2022)
Digital pathology (DP) offers potential for time efficiency gains over an analogue workflow however, to date, evidence supporting this claim is relatively lacking. Studies available concentrate on specific workflow points such as diagnostic reporting time, rather than overall efficiencies in slide logistics that might be expected. This is in part a result of the complexity and variation in analogue working, and the challenge therefore in capturing this. We have utilised RFID technology to conduct a novel study capturing the movement of diagnostic cases within the analogue pathway in a large teaching hospital setting, thus providing benchmark data for potential efficiency gains with DP. This technology overcomes the need to manually record data items and has facilitated the capture of both the physical journey of a case and the time associated with relevant components of the analogue pathway predicted to be redundant in the digital setting. RFID tracking of 1173 surgical pathology cases and over 30 staff in an analogue cellular pathology workflow illustrates the complexity of the physical movement of slides within the department, which impacts on case traceability within the system. Detailed analysis of over 400 case journeys highlights redundant periods created by batching of slides at workflow points, including potentially 2-3 hours for a case to become available for reporting after release from the lab, and variable lag-times prior to collection for reporting, and provides an illustration of patterns of lab and pathologist working within the analogue setting. This study supports the challenge in evidencing efficiency gains to be anticipated with DP in the context of the variation and complexity of the analogue pathway, but also evidences the efficiency gains that may be expected through a greater understanding of patterns of working and movement of cases. Such data may benefit other departments building a business case for DP.